P062 DOSE ESCALATION WITH ORIGINATOR INFLIXIMAB OR COMBINATION THERAPY WITH ORIGINATOR INFLIXIMAB AND IMMUNOMODULATORS SIGNIFICANTLY INCREASES RISK FOR SERIOUS ADVERSE EVENTS IN PEDIATRIC IBD – THE DEVELOP EXPERIENCE. (7th February 2019) - Veereman, Gigi; Busse, Christopher; Wang, Yanli; Izanec, James
Abstract: Background: DEVELOP is a multicenter, prospective, observational registry of the long-term safety and clinical status of 6070 pediatric patients with inflammatory bowel disease (IBD; Crohn's disease [CD], ulcerative colitis [UC], or indeterminate colitis [IC]) treated with originator infliximab (REM) and/or other medical therapies for IBD as part of routine clinical care. DEVELOP started in May 2007, is ongoing and has sites in the United States, Canada and in the EU (Belgium, Denmark, France, Germany, Italy, the Netherlands, and the United Kingdom). Our aim in this analysis was to examine how the risk and frequency of serious adverse events was affected by combination therapy with REM and immunomodulators as well as with dose escalation with REM. Methods: Physicians participating in the registry prescribe IBD treatments based on their usual clinical practice and standards of care. Patients are categorized into cohorts according to their prevalent or incident IBD medication exposure, including patients receiving therapy prior to enrollment and patients receiving therapy during registry follow-up. After the initial enrollment visit, data are obtained by the registry physician or designee every 6 months. The last data cut available, from June 30, 2018, assessed 29070 patient years (PY) of follow up. Results: An overview of SAEs by REM monotherapy or REM/immunomodulator (IMM) combination therapy during the last follow-up interval is presented by diagnosis (all IBD, CD, UC, and IC) and by geographic region for CD patients (EU and NA) in Table 1. Overall, patients on REM and IMM had a significantly larger number of SAE's (18.92 SAEs per 100 PY, 95% CI 14.57 to 24.16) compared to the REM monotherapy group (11.06 SAEs per 100 PY, 95% CI 8.89 to 13.59). The incidence of SAEs on REM monotherapy relative to REM/IMM combination therapy was numerically lower in each patient population (all IBD, CD, UC, and IC) and in CD patients from both geographic regions (EU and NA). In CD patients with at least 1 SAE, there was a statistically significant association between receiving > 5 mg/kg REM and having dose interval of < 8 weeks (Table 2). It should be noted that data on REM dose and frequency of administration were only available for exposure during participation in the registry, and not for exposure prior to enrollment into the registry. Conclusion: Combination therapy with REM and IMM was associated with statistically significantly more SAEs compared to REM monotherapy. CD patients with at least one SAE were more likely to be on more than 5 mg/kg and a dosing frequency of less than 8 weeks. Future analyses will examine potential effects of concomitant therapy, disease history and current disease activity on these results.